Motivasi Ikut Pendidikan Profesi Akuntansi dan Menjadi Akuntan Publik: Studi Empiris pada Mahasiswa S1 Akuntansi - Sandra Aulia; F. Fitriany; Viska Anggraita; A. Arywarti (Akuntabilitas, 2019)
The effectiveness of Accounting Professional Education goals is a big question for various parties. This study aims to analyze the factors that influence students’ interest in taking Accounting Professional Education and become Public Accountant. The procedure used in analyzing data uses Structural Equation Modeling (SEM). Total sample of 710 accounting undergraduate students. The results of this study indicate that career motivation factors, student perceptions of the accounting profession are positively related while the duration of education is negatively related to students’ interest in participating in PPAk. Interest in participating in PPAk, students ‘perceptions and duration of education, Type A and age characters are positively associated with students’ interest in becoming public accountants. This study contributes to the existing research in identifying factors that influence students’ interest in participating in Accounting Professional Education and being Public accountant